2002
DOI: 10.1093/emboj/cdf468
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the BAH-containing domain of Orc1p in epigenetic silencing

Abstract: contributed equally to this workThe N-terminal domain of the largest subunit of the Saccharomyces cerevisiae origin recognition complex (Orc1p) functions in transcriptional silencing and contains a bromo-adjacent homology (BAH) domain found in some chromatin-associated proteins including Sir3p. The 2.2 A Ê crystal structure of the N-terminal domain of Orc1p revealed a BAH core and a non-conserved helical sub-domain. Mutational analyses demonstrated that the helical sub-domain was necessary and suf®cient to bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
113
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 44 publications
7
113
0
Order By: Relevance
“…This is the same region of the BAH domain in the yeast Orc1-related Sir3 protein that binds to histone H4 present in a nucleosome ( Fig. 7B; Zhang et al 2002;Armache et al 2011). The histone H4 dimethylated peptide binds to an aromatic cage on one surface of the Orc1 BAH structure incorporating Tyr 63, Trp 87, Tyr 114, and Trp 119 (murine numbering) (red residues in Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is the same region of the BAH domain in the yeast Orc1-related Sir3 protein that binds to histone H4 present in a nucleosome ( Fig. 7B; Zhang et al 2002;Armache et al 2011). The histone H4 dimethylated peptide binds to an aromatic cage on one surface of the Orc1 BAH structure incorporating Tyr 63, Trp 87, Tyr 114, and Trp 119 (murine numbering) (red residues in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Of the mutations reported in human Orc1 in Meier-Gorlin syndrome, the three mutations (F89S, R105Q, and E127G) occurred within the CID that contains a bromo-associated homology (BAH) domain (Fig. 5A, top panel; Zhang et al 2002;Kuo et al 2012). Most Meier-Gorlin syndrome patients (seven out of 11 recently characterized) have an Orc1 with a mutation that changed an arginine at amino acid 105 to a glutamine (R105Q) (de Munnik et al 2012).…”
Section: Meier-gorlin Mutations Differentially Alter Orc1 Inhibition mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of HMR-E, a silencer that is necessary and sufficient to target silent chromatin to HMR, has established that the primary role for ORC in silencing is to recruit Sir1p to the silencer through direct protein-protein interactions between the Orc1p subunit of ORC and Sir1p (6)(7)(8)(9)(10)(11). ORC-bound Sir1p nucleates and͞or stabilizes a silent chromatin domain through direct protein-protein interactions with other Sir proteins, in particular Sir4p (7,11).…”
mentioning
confidence: 99%
“…Molecular and genetic analyses have shown that the Sir1p͞ ORC interaction occurs through direct contacts between discrete domains within each protein. In ORC, the key interaction domain is the N-terminal bromo-adjacent homology (BAH) domain of Orc1p (10,13). BAH domains are conserved in Orc1 homologs across species (14) and are found in several other chromatin-associated proteins (15,16), suggesting that BAH domains play broad roles in regulating the structure and function of chromosomes.…”
mentioning
confidence: 99%